Pediatric Specialty Dental and Oral Health Care Model on Oral Therapist Compliance and Child Anxiety - Utomo, Suprih; Santoso, Bedjo; Fatmasari, Diyah; Aprillia, Zita; Ningtyas, Endah Aryati Eko (Jurnal Kesehatan Gigi, 2024)
Background: Oral Therapists in pediatric dentistry services are to provide oral health care contained in Kepmenkes Number HK.01.07/MENKES/1513/2022, with stages: Assessment, diagnosis, planning, implementation and evaluation. The implementation of service actions in hospitals, oral therapists only play a role in the intervention stage (assisting pediatric dental specialists), while at the stages of assessment, diagnosis, planning and evaluation in care services are carried out by general nurses (application of complete nursing care) this is because dental therapists do not yet have dental health care.Objective: To develop a pediatric dentistry oral health care model for dental therapist compliance and children's anxiety.Methods:  This research design uses RD. The sample was divided into 2 groups, the oral health care model in pediatric patients with mesiodens tooth extraction cases as many as 10 respondents and dental therapists as many as 10 respondents on compliance. Analysis using the Wilcoxon test.Results: The oral health care model effectively reduces children's anxiety. The correlation value of R square is 0.583. The coefficient of determination (R Square) is 0.340, that the influence of the model implementation compliance variable by oral therapist on the variable child anxiety in the act of tooth extraction in mediocre cases is 34%. The F value was found to be 4.121 with a significance level of 0.077 (0.05).Conclusion:  The oral health care model for pediatric tooth extraction with mesiodens cases is feasible and its application is effective in increasing the compliance of oral therapists, reducing children's anxiety in accepting pediatric tooth extraction.